Pengaruh Tekanan, Kesempatan, Rasionalisasi Dan Kapabilitas Terhadap Kecenderungan Kecurangan Pengelolaan Keuangan Desa - Putri, Ni Kadek Ayu Verayanti; Ayu, Putu Cita; Pratiwi, Ni Putu Trisna Windika (Hita Akuntansi dan Keuangan, 2025)
Fraud in village financial management carried out by the government, especially at the village level, has often occurred in Indonesia since the decentralization of development to the village level, so that the village government has primary control over funds allocated through village funds and village fund allocations. The aim of this research is to determine the influence of pressure, opportunity, rationalism and capability on the tendency for fraudulent village financial management (Case Study in Banjar District Village Government). Population and sample used was 102 employees of the Banjar District Village Office. The data analysis used multiple linear regression,. The results of the analysis show that pressure has effect on the variable tendency for fraud in managing funds in Banjar District Village, opportunity has effect on the variable of tendency for fraud in managing funds in Banjar District Village, rationalism has a positive effect on the variable of tendency for fraud in managing funds in Banjar District Village. and capability has a effect on the variable tendency for fraudulent management of Banjar District Village funds.